Special Exercises According to Refereeing and It's Effect on Developing Some Physical Abilities Of First Class Basketball Referees in Baghdad - Abedulsattar, Muhanned; Ali, Nooralddin (Journal of Physical Education, 2017)
Basketball is one of the most popular and popular games that have a large audience both globally and locally because of the magic it contains in terms of performance. For this sport to be a success, fundamental factors must exist and these factors is the referee. The referee plays a large and important role in the success of the game and the establishment and application of rules. The research aimed at identifying the effect of special on the development of referee's physical abilities. The researcher used the experimental method. The subjects were (12) first class basketball referees. The researcher recommended using special exercises due to their great role in developing the physical abilities of first class basketball referees